Improvisations Technique in the Teaching of Speaking - Fauzan, Umar (Media Akademika, 2012)
Making students able to speak English is not an easy thing. Many English learners are reluctant and unmotivated. Some students will not talk because they are too shy or have such high levels of anxiety over speaking. Perhaps, they are shy because they are afraid of making mistakes or their friends will laugh at them. They are also anxious because they had not many changes to speak or because the teacher always gave critics and correct their mistakes right away. One of the strategies that a teacher could use improving their motivation in speaking is improvisations technique. Improvisations technique as one of the types of drama can be chosen because it provides a useful springboard for reallife language use. The students have a big chance to practice speaking English freely in Improvisations technique. Improvisation is the strategy of teaching where students are given roles to perform dialogues or conversation using their own word or sentences based on the conversation situation/topics on clue cards given. First, the teacher explains the situations/topics on the role-card. Then the teacher groups the students, there are 3 or 4 for each group. After receiving the role-card, the students create the plot and prepare to perform. They have no much time to prepare; it is only 2 â 4 minutes. After that, they perform it. Thereâs no script dialogue, itâs spontaneous speaking performance. The students use their own knowledge, words, and sentences in improvisations. Improvisations technique is a good way to improve studentsâ confidence to speak English. By having self-confidence, the students will be able to talk much in English. Talking much in English has a big contribution to build their fluency. Then, the studentsâ fluency is a high way to improve their speaking ability. In the implementation of improvisations, the teacher should be well-prepared before teaching speaking using improvisations technique in the English classroom. The teacher preparation will affect the implementation of improvisations its self. The success on improvisations is depending on how a teacher makes good preparation for some important elements of using improvisations, they are seat arrangement, Classroom properties usage, the role-play cards, the speaking aids, and the studentsâ involvement.